“They looked at me like I am a virus”: how survivors cope with COVID-19 stigma during the early stage of pandemic - Sulistyawati Sulistyawati; Rokhmayanti Rokhmayanti; Budi Aji; Siwi Pramatama Mars Wijayanti; Tri Wahyuni Sukesi; Surahma Asti Mulasari (International Journal of Public Health Science (IJPHS), 2023)
COVID-19 has shocked everyone globally, with fears of contracting the disease and the other socio-economic impacts. The noticeable impact at the beginning of the COVID-19 pandemic was the emergence of mental health disorders in the community, especially for patients, namely the stigma labeled on them. This study aimed to explore the COVID-19 survivors’ experience since they were declared positive and isolated, including the stigma they faced in the early stage of the pandemic, using a phenomenology approach. Eight informants selected through purposive sampling were contacted via in-depth online interviews during September-December 2020. All interviews were recorded, transcribed, and analyzed using thematic analysis. During the investigation, this research found two themes: encountering unpleasant impacts when contracting COVID-19 and coping strategies related to the impact. The negative stigma affected the informants’ psychology and economics. Most informants took a religious/belief method to cope with the adversity, such as surrendering to God, and some reported ignoring the stigma. After one year of the pandemic, the stigma has dramatically reduced. However, continuous education in the community is needed to prevent stigmatization of COVID-19 survivors since the pandemic continues and scientific development in fighting this disease is ongoing. This research provides lessons learned to the community and related parties that mental health must also be a concern beyond the rapid response to disease control in a health emergency.